2018
DOI: 10.4103/ejd.ejd_410_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Er: YAG laser on the shear bond strength of conventional glass ionomer and BiodentineTM to dentine

Abstract: Objectives:The purpose of this study was to determine if Er: YAG laser etching improves the shear bond strength (SBS) of Biodentin™ and GC Fuji IX® to dentine.Materials and Methods:Forty human dentine specimens were standardized and embedded in stone. The specimens were randomized into four groups (n = 10). Twenty samples were treated with the Er: YAG laser radiation and 10 of these restored with GC Fuji IX® and 10 with Biodentine™. The remaining 20 specimens acted as controls (no laser treatment); 10 were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In our study, the SEM evaluation visualized Biodentine ® residues on the dentin surfaces of the samples and also showed that the tubules were occluded with these residues. In a similar way, some studies also reported that Biodentine ® extended deep into dentinal tubules and the residues thereby occluded the tubules (Aljdaimi, Devlin, & Dickinson, 2018;Atmeh et al, 2012). Shalan, Awad, and El-Fallal (2012) reported that ferric sulfate and formocresol decreased the shear bond strength of composite resin cement to primary tooth dentin, thereby leading to a negative effect on the molecular structure of the adhesive system.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, the SEM evaluation visualized Biodentine ® residues on the dentin surfaces of the samples and also showed that the tubules were occluded with these residues. In a similar way, some studies also reported that Biodentine ® extended deep into dentinal tubules and the residues thereby occluded the tubules (Aljdaimi, Devlin, & Dickinson, 2018;Atmeh et al, 2012). Shalan, Awad, and El-Fallal (2012) reported that ferric sulfate and formocresol decreased the shear bond strength of composite resin cement to primary tooth dentin, thereby leading to a negative effect on the molecular structure of the adhesive system.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, the SEM evaluation visualized Biodentine ® residues on the dentin surfaces of the samples and also showed that the tubules were occluded with these residues. In a similar way, some studies also reported that Biodentine ® extended deep into dentinal tubules and the residues thereby occluded the tubules (Aljdaimi, Devlin, & Dickinson, 2018; Atmeh et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that altering the surfaces of the teeth by lasers improves the adhesion of the restorations (20)(21)(22). In addition, there is little information in the literature about the sealing ability of Class V cavities prepared with Er: YAG laser and restored with CGICs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to numerous advantages, this laser has been suggested for enamel and dentin surface treatment to enhance the bond strength (7). Considering the numerous advantages of application of Er,Cr:YSGG laser in pediatric dentistry such as optimal acceptance by children and parents due to its minimal invasiveness and higher cooperation of pediatric patients during restorative treatments with laser (3), the low bond strength of GI to tooth surface, lack of sufficient studies regarding the efficacy of Er,Cr:YSGG laser for dentin surface preparation, and the controversial results of previous studies (8,9), this study was designed to assess the microshear bond strength of GI to primary dentin following surface preparation by bur in comparison with Er,Cr:YSGG laser irradiation.…”
Section: Introductionmentioning
confidence: 99%